Application Tool for Two-Variable Cost Allocation for Small Urban, Rural, and Tribal Transit Agencies. Issue 4 (April 2020) - Hansen, Todd; Walk, Michael; Tan, Shuman
The paper presents the development and methodology of application tools for use in transit agency cost allocation. Researchers worked with the National Rural Transit Assistance Program to develop the Two-Variable Cost Allocation Calculator applications as a resource for small transit agencies. Reports and guidance on cost allocation were reviewed to identify key considerations for application design, was also informed by previous experience with transit agencies for examples of cost and data considerations with respect to agency size, travel mode, and type of service. The applications use a two-variable methodology of vehicle hours and miles to allocate variable costs for each service, then allocate fixed costs according to the proportions of variable costs. The applications also provide a process to sub-allocate costs for shared-ride demand responsive services using passenger hours and miles data. A common set of data requirements needed to run the applications into groups of service, financial, and operational data was developed. The applications use standard definitions of data elements from the National Transit Database and Federal Transit Administration to streamline the data needed in the application with existing reporting requirements. The applications are designed for ease of use by small transit agencies with limited staff and different levels of training in data collection or financial management. The applications allow small transit agencies to specify aspects of service information to be used in cost allocation while relying on the applications to sort expenses into appropriate cost function categories, calculate costs by service type, and generate summary reports and performance metrics.